Isolation and characterization of polymorphic microsatellite markers in Tetranychus urticae and cross amplification in other Tetranychidae and Phytoseiidae species of economic importance - Sabater-Munoz, Beatriz; Pascual-Ruiz, Sara; Gómez-Martínez, María A.; Jaques, Josep A.; Hurtado-Ruiz, Mónica A. (2017)
Tetranychus urticae Koch is a cosmopolitan phytophagous mite considered as the most polyphagous species among spider mites. Population genetic studies using molecular markers such as microsatellites have proven to be extremely informative to address questions about population structure, phylogeography and host preferences. The aim of this study was to increase the available molecular tools to gain insight into the genetic structure of T. urticae populations of citrus orchards, which might help in their management. Five microsatellite DNA libraries were developed using probes with the motifs CT, CTT, GT and CAC following the FIASCO protocol. Positive clones, those that included the insert with the microsatellite, were detected using the PIMA-PCR technique. Combinations of primers were designed on 22 out of 32 new microsatellites loci and their polymorphism was tested in four populations sampled along the eastern coast of Spain. Eleven successful amplifications were obtained. Cross amplification was tested in the tetranychids Aphlonobia histricina, Eutetranychus banksi, E. orientalis, Oligonychus perseae, Panonychus citri, Tetranychus evansi, T. okinawanus and T. turkestani, and the phytoseiids Amblyseius swirskii, A. cucumeris, A. andersoni, Euseius stipulatus, Neoseiulus barkeri, N. californicus, Phytoseiulus persimilis and Typhlodromus phialatus. Eight successful cross amplifications were obtained.